Rancang Bangun Robot Pemotong Rumput Berbasis Arduino Menggunakan Smartphone Android - Bellarmino Wira Permana; Sundari Retno Andani; Ika Purnama Sari; Dedy Hartama; Jalaluddin Jalaluddin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
House chores that people do is still using human power, one of which is taking care of the yard in terms of cutting grass, which still uses simple tools such as knives or grass shears so that it is enough to spend energy and time. Technology is very appropriate in helping the community's workload, for example, an Arduino based lawn mower robot that is controlled via an android device with a Bluetooth HC-06 device connection then equipped with an L298n driver as a wheel motor drive, and the robot is equipped with a cutting blade made of nylon string a distance of 0.9 inches from the ground, we can control the robot through an android device via navigation commands on the application. The robot can move forward, backward, turn right, turn left, and the robot cuts the grass cut according to the command.